Dynamic lighting schedules to facilitate circadian adaptation to shifted timing of sleep and wake. Issue 1 (25th May 2022) - Rahman, Shadab A.; St. Hilaire, Melissa A.; Grant, Leilah K.; Barger, Laura K.; Brainard, George C.; Czeisler, Charles A.; Klerman, Elizabeth B.; Lockley, Steven W.
Abstract: Circadian adaptation to shifted sleep/wake schedules may be facilitated by optimizing the timing, intensity and spectral characteristics of light exposure, which is the principal time cue for mammalian circadian pacemaker, and possibly by strategically timing nonphotic time cues such as exercise. Therefore, circadian phase resetting by light and exercise was assessed in 44 healthy participants (22 females, mean age [±SD] 36.2 ± 9.2 years), who completed 8‐day inpatient experiments simulating night shiftwork, which included either an 8 h advance or 8 h delay in sleep/wake schedules. In the advance protocol ( n  = 18), schedules were shifted either gradually (1.6 h/day across 5 days) or abruptly (slam shift, 8 h in 1 day and maintained across 5 days). Both advance protocols included a dynamic lighting schedule (DLS) with 6.5 h exposure of blue‐enriched white light (704 melanopic equivalent daylight illuminance [melEDI] lux) during the day and dimmer blue‐depleted light (26 melEDI lux) for 2 h immediately before sleep on the shifted schedule. In the delay protocol ( n  = 26), schedules were only abruptly delayed but included four different lighting conditions: (1) 8 h continuous room‐light control; (2) 8 h continuous blue‐enriched light; (3) intermittent (7 × 15 min pulses/8 h) blue‐enriched light; (4) 8 h continuous blue‐enriched light plus moderate intensity exercise. In the room‐light control, participants received dimmer white light for 30 min before bedtime, whereas in the other three delay protocols participants received dimmer blue‐depleted light for 30 min before bedtime. Both the slam and gradual advance protocols induced similar shifts in circadian phase (3.28 h ± 0.37 vs. 2.88 h ± 0.31, respectively, p  = .43) estimated by the change in the timing of timing of dim light melatonin onset. In the delay protocol, the continuous 8 h blue‐enriched exposure induced significantly larger shifts than the room light control (−6.59 h ± 0.43 vs. −4.74 h ± 0.62, respectively, p  = .02). The intermittent exposure induced ~60% of the shift (−3.90 h ± 0.62) compared with 8 h blue‐enriched continuous light with only 25% of the exposure duration. The addition of exercise to the 8 h continuous blue‐enriched light did not result in significantly larger phase shifts (−6.59 h ± 0.43 vs. −6.41 h ± 0.69, p  = .80). Collectively, our results demonstrate that, when attempting to adapt to an 8 h overnight work shift, delay shifts are more successful, particularly when accompanied by a DLS with high‐melanopic irradiance light stimulus during wake.